Effects of combined training during the COVID-19 pandemic on metabolic health and quality of life in sedentary workers: A randomized controlled study - Silva, Fernanda M.; Duarte-Mendes, Pedro; Carvalho, Eugénia; Soares, Carlos M.; Farinha, Carlos; Serrano, João; Paulo, Rui; Massart, Alain; Rodrigues, Rafael N.; Teixeira, Ana M.; Ferreira, José Pedro (Frontiers in Public Health, 2022)
This study aimed to analyze the effects of a combined training (CT) program performed during the first national lockdown due to the COVID-19 pandemic on body composition, metabolic profile, quality of life and stress in sedentary workers, and examines whether changes in the metabolic profile are associated with changes in health-related outcomes which are modifiable by exercise. We evaluated 31 sedentary workers (48.26 ± 7.89 years old). Participants were randomly assigned to a CT group (i.e., performed 16 weeks of exercise) or to a non-exercise control group. The CT program consisted of 16-week of resistance and aerobic exercise. Body composition, glycemic and lipidic profiles, cardiorespiratory fitness (CRF), health-related quality of life and stress levels were assessed pre- and post-intervention. After the intervention period, the CT group demonstrated significantly lower waist and hip circumference (p < 0.05) values than the control group. The control group significantly increased the fasting glucose and HOMA-IR after 16 weeks follow-up (+4.74 mg/dL, p = 0.029; and +0.41 units, p = 0.010, respectively), whiles no significant changes were observed in the CT group in the same parameters (+3.33 mg/dL, p = 0.176; and +0.04 units, p = 0.628, respectively). No changes were observed in the lipid profile for either group (p > 0.05). A significant positive relationship was detected between the change in BMI with the changes in insulin and HOMA-IR (r = 0.643, p = 0.024; and r = 0.605, p = 0.037, respectively). In addition, the changes in CRF were negatively associated with the changes in total cholesterol (r = -0.578, p = 0.049). We observed differences between groups on perceived stress levels and physical, psychological, and environmental domains of quality of life, with the CT group showing better results. Moreover, the CT group improved perceived life satisfaction (+3.17 points, p = 0.038). The findings of the present study suggest that the participants who remained physically active during the first pandemic-related lockdown were able to mitigate the deleterious effects associated with a sedentary lifestyle.